Komo puede ser? The Judeo-Spanish Riddle - Alexander, Tamar (MiKAN, 2007)
The aim of this article is to examine the Judeo-Spanish (Ladino) riddle, to classify its types and to analyze its characteristics and its place and function in the group culture. This subject has hardly been researched. The article is based on a corpus of 114 riddles from printed sources and the author’s fieldwork. This is quite a small corpus, as riddles are hardly used anymore. Analyzing the riddles of one group can provide a key to understanding its culture and ethnic identity. On the one hand, it permits an understanding of the group norms, ideas, values and didactic aims. On the other, the uniqueness of the riddle is that it also expresses a disapproval, protest and reevaluation of those norms. Yet, by offering a solution at the end of the riddle, it reinforces the group norms. The corpus of riddles represented in this article expresses these two contradictory directions. The riddles reflect the different levels of relationships in the family from different aspects: It can express erotic desires when riddles are posed among women, or their protest against the traditional obligations of women towards their husbands. They can express aggression and confrontation among husbands and wives or authority and teaching values among parents and children. Everyday life is reflected in the text of the riddle, by the description of objects, animals or human traits and looks as part of the Sephardic reality. But above all the ethnic identity is expressed by posing the riddles in Ladino, the unique language of the group. Performing a riddle and offering the solution requires a mastery of the language. The riddle uses rhymes, rhythm, and poetic devices such as puns, metaphors and similes. Performing a riddle always requires at least two people, who are holding an unequal dialogue between the one who asks the question (and already knows the answer) and the one who tries to guess the answer though the question is deliberately confusing and ambiguous. Performing a riddle requires a special situation, almost like a ritual, when two or more people accept the role of the riddle and the active audience. The process of riddling needs a constant creativity to invent new riddles, as one that is already known is no longer usable. Coupled with the need for a broad knowledge of the language, this might be the reason why Ladino riddles have almost disappeared as a live genre. It seems that among a group whose language is no longer alive, riddles have lost their place.